Análise de uso e cobertura do solo no município de Parelhas/RN - Cosme Júnior, Sebastião (2011)
The human interference in the semiarid region of Seridó Potiguar has promoted the increase of degraded areas. The economic dynamic that was established in the Seridó territory, especially after the fall of the trinomial cattle-cotton-mining in the 70s and 80s of the 20th century as pillars of the regional economy, resulted in an accelerated process of erosion of natural resources. The municipalities of the Seridó region have been spatially reordered by this new economic dynamic, marked by the growth of existing enterprises, and the development of new agricultural practices. One of the municipalities in the region that restructured its territorial space with the emergence of new agro-industrial activities was the town of Parelhas. With the demise of the trinomial cattle-cotton-mining in the 1980s, other productive activities were intensified from the 1990s, amongst them, pottery, responsible for the vegetal extraction for use as energy source. This recent economic and spatial restructuring in the region, reflected in the Parelhense municipal territory, required new productive ingredients responsible for the modification of past production relations that were based on cattle, cotton and mining. By that a process of exploring the environment was unleashed, especially the native vegetation, in an uncontrolled manner. In this context, the objective of this study was to survey and detect deforestation in the areas of Caatinga vegetation, used indiscriminately as energy supply for new agricultural practices, using remote sensing techniques based on the quantification of the Normalized Difference Vegetation Index / NDVI, Soil-Adjusted Vegetation Index / SAVI, surface temperature and rainfall data in the years 1990 and 2010. The results indicated that SAVI values above 0.2 in 1990 and 2010 represent the areas with the highest density of vegetation that occur exclusively along the major drainages in the town and areas of higher elevations. The areas between the ranges of values from 0.5 to 0.15 SAVI are areas with poor vegetation. On the other hand the highest values of temperature are distributed in the western and southeastern parts of the township, usually in places where the soil is exposed or there is sparse vegetation. The areas of bare soil decreased in extension in 2010 at 11, 6% when related to 1990, this was caused by a higher rainfall intensity in the first half of 2010, but no regeneration of vegetation occurred in some places in the western and southeastern areas of the municipality today, due to the extraction of firewood to fuel the furnaces of industries in town